posted on Jan, 29 2006 @ 06:59 PM
I just worked it out, and here is what I did...
Let x and y be the two numbers in question. Then, you need to find x and y so that x*y = -2 and x+y=5
Rearrange the second equation so you have y=5-x and substitute this into the first equation to get x*(5-x)=-2 Multiply it out and you get 5x-x^2=-2
If you rearrange that to get a quadratic equation you get x^2-5x-2=0 Then you can solve for x using the quadratic formula, or any other method for
solving this sort of equation, and get two possibilities for x.
x = [5 + sqrt(33)]/2 = 5.372281323... (possibility 1)
x = [5 - sqrt(33)]/2 = -0.372281323... (possibility 2)
If you put x=5.37 into either one of the first two equations (xy=-2 or x+y=5) you get that y=-0.372281323, and if you put x=-0.37 into the equations,
you get y=5.372281323.
So the two numbers are 5.372281323 and -0.372281323, or [5+sqrt(33)]/2 and [5-sqrt(33)]/2
edit to put in some square brackets [] to increase clarity instead of all () type brackets
another edit to say that sqrt(33) means the square root of 33
[edit on 29-1-2006 by DragonsDemesne]
[edit on 29-1-2006 by DragonsDemesne]